"LOP EN RESING" A SHORT FILM MEDIA DESIGN AS A PART OF SOCIAL CAMPAIGN TO RAISE AWARENESS FOR TEENAGERS ON ILLEGAL RACING IN BANDUNG - Haq, Alvein Dhiwaul; Bastari, Rendy Pandita; Aditya, Dimas Krisna (eProceedings of Art & Design, 2024)
Illegal racing among teenagers is a serious concern in many cities, including Bandung, Indonesia. This research explores the use of short films as a tool to prevent illegal racing among teenagers in Bandung. Research methods include interviews, literature studies, questionnaires, and observation. The results of the research are expected to provide insight into the effectiveness of short films in changing the attitudes and behavior of adolescents regarding illegal racing. The findings of this study will benefit policy makers, educators and practitioners seeking to prevent illegal racing among youth in Bandung, Indonesia and elsewhere. Keywords: Illegal racing, teenagers, short film, media design, Bandung